PHYSICAL AND ANTIOXIDANT PROPERTIES OF TWO ALGERIAN DATE FRUIT SPECIES (PHOENIX DACTYLIFERA L. AND PHOENIX CANARIENSIS L.) - Djouab, Amrane; Benamara, Salem; Gougam, Hassina; Amellal, Hayet; Hidous, Karima (Emirates Journal of Food and Agriculture, 2017)
The present comparative study aimed to investigate for the first time some physical and antioxidant properties of date fruits from Phoenix dactylifera L. (cv. Mech-Degla) (MD) and Phoenix canariensis L. (CRD) palms. The physical properties of whole date fruits and date fruit seeds were analyzed separately. But the antioxidant potential (AP), evaluated throughout total phenolic content (TPC), reducing power (RP) and antiradicalar activity (AA) towards the stable free radical 2,2-Diphenyl-1-picrylhydrazyl (DPPH) were analyzed in different tissues of date fruit fleshes. Results showed that linear dimensions, equivalent diameter, volume, mass, sphericity, surface area, bulk density, porosity, angle of repose and hardness, were statistically different (p<0.05) in the two cases considered (whole fruit and seeds). Globally, canariensis L. red date and its constitutive tissues (peel, yellow and white flesh parts) showed a greater RP and greater 2,2-Diphenyl-1-picrylhydrazyl scavenging effect, compared with tissues of Phoenix dactylifera L. date palm variety. Also, a positive linear correlation of type TPC/RP (R2 =0.983) and TPC/AA (R2 =0.853) was observed. So, the underused Phoenix canariensis L. red date as wild fruit may be employed as natural additive in food and non-food formulations.